Peran Guru BK dalam Memberikan Informasi Karir melalui Bimbingan Karir terhadap Siswa Kelas IX di MTs. Swasta Al- Ihsan Maryke - Ikhsan Fathoni; Irwan S; Alfin Siregar (Institut Nalanda, 2024)
This research aims to examine the role of guidance and counseling teachers in providing career information through career guidance to class IX students at Al-Ihsan Maryke Private MTs, located on Jln. Education No.1 Maryke, Maryke Plantation, Kutambaru, Langkat Regency, North Sumatra. The research method used is qualitative with a focus on how guidance and counseling teachers convey information regarding career choices and educational paths after graduation. The research results show that guidance and counseling teachers at Al-Ihsan Maryke Private MTs play a vital role by providing an overview of various professions and their requirements, as well as facilitating group discussions and question and answer sessions. They also invite practitioners from various fields to provide direct insight to students. However, there is a lack of depth of information and personalization of guidance. The career guidance provided is often felt to be too general and not suited to students' specific needs. Many students feel that the information presented is not in-depth enough and is difficult to apply to their personal situations, so they have difficulty connecting career choices with their interests and talents. To increase the effectiveness of coaching, a more structured and detailed approach is needed as well as more personalized coaching sessions. This is expected to help students plan concrete steps for their future and make better decisions regarding education and career.